PENGARUH PENAMBAHAN KEONG MAS (Pomacea canaliculata) TERHADAP PERUBAHAN SIFAT KIMIA ULTISOL - Oktanis Emalinda; Adnawita Adnawita; Eti Farda Husin (Jurnal Solum, 2009)
To look for the effect of gold snail (Pomacea canaliculata) addition on soil nutrition level, a series of pot experiment was conducted in Faculty of Agriculture and P3IN laboratories from March to June 2008. This study used completely randomized design with 2 kinds of treatments. First iwas gold snail composition (A1 = snail shell, A2 = snail body, and A3 = whole snail) and incubation period (B1 = 2 weeks, B2 = 3 weeks, and B3 = 4 weeks). The results showed that these treatments affect some of soil chemical properties. Soil pH changed from acid to slightly acid, total nitrogen rose from low to medium, exchangeable base cations also increased. On the other hand, exchangeable aluminum (Al) decreased. Interaction between the treatments successfully increased organic carbon, available phosphorous, and cation exchange capacity. The best treatment combination was between body composition of gold snail and a four-week incubation period.Key Words: gold snail, Ultisols, soil chemical characteristics